Measuring and Improving Diagnostic Safety in Primary Care: Addressing the “Twin” Pandemics of Diagnostic Error and Clinician Burnout - Olson, Andrew P. J.; Linzer, Mark; Schiff, Gordon D. (Journal of general internal medicine : JGIM, 2021)
Diagnostic errors are a source of unacceptable harm in health care. However, improvement efforts have been hampered by the lack of valid measures reflecting the quality of the diagnostic process. At the same time, it has become apparent that the healthcare work system, particularly in primary care, is chaotic and stressful, leading to clinician burnout and patient harm. We propose a new construct that health systems and researchers can use to measure the quality and safety of the diagnostic process that is sensitive to the context of the health care work system. This model focuses on three measurable practices: considering “don’t miss” diagnoses, looking for red flags, and ensuring that clinicians avoid common diagnostic pitfalls. We believe that the performance of clinicians with respect to these factors is sensitive to the health care work system, allowing for context-dependent measurement and improvement of the diagnostic process. Such process measures will enable more rapid improvements rather than exclusively measuring outcomes related to “correct” or “incorrect” diagnoses.